2008
DOI: 10.1007/s12253-008-9104-2
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Prostate-Specific Membrane Antigen (PSMA) Expression in Prostate Carcinoma with Distant Metastasis

Abstract: Prostate-specific membrane antigen (PSMA) is a transmembrane protein that is overexpressed in advanced stage prostate adenocarcinomas. As a novel target for in vivo prognostic and therapeutic approaches, the distribution pattern of PSMA in primary and metastatic tumors is of significant interest. In this study we addressed the cellular distribution and heterogeneity of PSMA expression. Paraffin-embedded sections of 51 patients with primary prostate carcinoma and distant metastases were evaluated. Immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
240
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(252 citation statements)
references
References 15 publications
8
240
0
4
Order By: Relevance
“…Other authors also reported a high sensitivity of 85-100% in lymph node and distant metastases. 30,31 Until a few years ago, detection of TMPRSS2-ERG fusion was only possible using fluorescence in situ hybridization. Since TMPRSS2-ERG fusion highly correlates with ERG overexpression, the newly available monoclonal antibodies displaying ERG overexpression open up the opportunity for routine utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors also reported a high sensitivity of 85-100% in lymph node and distant metastases. 30,31 Until a few years ago, detection of TMPRSS2-ERG fusion was only possible using fluorescence in situ hybridization. Since TMPRSS2-ERG fusion highly correlates with ERG overexpression, the newly available monoclonal antibodies displaying ERG overexpression open up the opportunity for routine utilization.…”
Section: Discussionmentioning
confidence: 99%
“…However, especially in patients with PSA values below 3 ng/mL, the detection rate is only 40%-60% (3,4,7). Recently, a new molecular probe targeting, for example, the gastrinreleasing peptide receptor or the prostate-specific membrane antigen (PSMA), has been developed (10)(11)(12). PSMA is a membrane-bound enzyme with significantly elevated expression in PC cells in comparison to benign prostatic tissue (13).…”
mentioning
confidence: 99%
“…PSMA is a transmembrane protein that is highly overexpressed (100-to 1,000-fold) on almost all PC tumors (16)(17)(18)(19). Only 5%-10% of primary PC lesions have been shown to be PSMA-negative (20,21).…”
mentioning
confidence: 99%